Reimagining Trade Corridors: Regulatory Dynamics and Sustainability in Global Commerce - Muharam, Husni; Wufron, Wufron (Sinergi International Journal of Logistics, 2023)
This narrative review explores the regulation of international trade, focusing on transport corridor development and its impact on sustainable global commerce. It synthesizes literature from Scopus, Web of Science, and Google Scholar, using keywords like "international trade," "transport corridors," "sustainability," and "policy regulation." Studies were selected for thematic relevance, methodological quality, and regional diversity, including cases from China, Kenya, Russia, and the EU. The review finds that while liberalized trade and infrastructure investment bring economic benefits, they also present environmental and social challenges. It highlights disparities in regulatory standards, the role of institutions in policy-making, and the need for civil society involvement. Developed countries lead in environmental governance, while developing nations face implementation obstacles. The findings are linked to theories of trade liberalization, dependency, global governance, and social capital. The study recommends data-driven policies, multi-stakeholder collaboration, and integrating sustainability into trade regulation to promote inclusive and environmentally responsible global trade.